(untitled) (Eurasian Journal of History, Geography and Economics, 2026)
This article provides a systematic analysis of how the history and culture of the early Aral Sea Saka tribes are reflected in ancient written and epigraphic sources. The research comprehensively examines data ranging from the Zoroastrian sacred text, the Avesta, and epic traditions to the cuneiform inscriptions of the Achaemenid dynasty and accounts by classical authors. It elucidates the semantic and etymological genesis of the ethnonym “Sakā”, evaluates long-debated totemic theories in scholarship, and explores the ethno cultural proximity between the Sakas and ancient Khorezmians regarding garments, weaponry, and attributes. Furthermore, through a comparative source analysis, the study evaluates the geopolitical prominence of the Saka communities as a northeastern satrapy of the Achaemenid Empire and examines their role as equal allies in the Greco-Persian Wars and the campaigns of Alexander the Great. By cross-referencing and comparing written records with the archaeological data from the Khorezm ArchaeologicalEthnographic Expedition (KAEE), this study integrates reliable data into a cohesive and objective historical framework.